2014
DOI: 10.14527/pegegog.2014.009
|View full text |Cite
|
Sign up to set email alerts
|

The examination of relationships between emotional intelligence levels and creativity levels of pre-service teachers in the teaching-learning process and environments

Abstract: The aim of this study is to examine the relationship between emotional intelligence levels and creativity levels of pre-service teachers in the process of constructing educational system in Turkey. In the study, mixed methods which include qualitative and quantitative data were used. The study was done in 2011-2012 academic year with the participation of the students of Muğla University, Faculty of Education, Departments of Elementary Science Teaching, Elementary School Teaching, Pre-School Teaching, Elementar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…In this context, it is believed that investigating the studies that focus on teacher candidates' creativity will be beneficial. Literature presents studies that both point to (İsleyen and Kucuk, 2013;Duman et al, 2014) and insignificant differences (Emir et al, 2004;Gorgen and Karacelik, 2009) in the creativity levels of teacher candidates based on departments they attend. Different results were obtained in studies that focus on teacher candidates' creativity levels based on gender.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, it is believed that investigating the studies that focus on teacher candidates' creativity will be beneficial. Literature presents studies that both point to (İsleyen and Kucuk, 2013;Duman et al, 2014) and insignificant differences (Emir et al, 2004;Gorgen and Karacelik, 2009) in the creativity levels of teacher candidates based on departments they attend. Different results were obtained in studies that focus on teacher candidates' creativity levels based on gender.…”
Section: Discussionmentioning
confidence: 99%
“…Different results were obtained in studies that focus on teacher candidates' creativity levels based on gender. Duman et al (2014) and İsleyen and Kucuk (2013) found that creativity levels of teacher candidates did not show meaningful differences according to gender whereas Gok and Erdogan (2011) determined that creativity of female teacher candidates were higher. In their research that examined the studies on creativity in national educational programs, Summak and Aydın (2011) found that gender does not have a significant effect on teacher candidates' creativity levels in general.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous past research studies have extensively utilized the effect model to explore how emotional intelligence, personality traits and employee creativity are interconnected (Duman et al, 2014;Ezzi et al, 2016;Mobbs, 2020;Nawi et al, 2018;Zulkifli et al, 2020). However there has been limited focus, on measuring personality traits as mediators between intelligence and creativity.…”
Section: Discussionmentioning
confidence: 99%
“…The literature reported different findings indicating that the EI concept may change from culture to culture. For instance, while Duman et al [20] found gender differences in EI among pre-service teachers in Turkiye, with females scoring higher than males, Dimitriu et al [19] reported no significant differences in EI levels based on gender, age, or specialty among their Romanian participants. Such inconsistencies showed the complexity of EI as a construct and its potential predisposition or resistance to demographic variables.…”
Section: Understanding Emotional Intelligence Achievement Motivation ...mentioning
confidence: 98%
“…Investigating the relationship between EI and demographic characteristics helps us to understand how individual and socio-cultural factors influence one to manage emotions, empathize with others, and navigate social difficulties. Studies across different cultures and countries [17][18][19][20][21] emphasized the importance of examining the relationship between EI and demographic variables (i.e., gender, income, education level). The literature reported different findings indicating that the EI concept may change from culture to culture.…”
Section: Understanding Emotional Intelligence Achievement Motivation ...mentioning
confidence: 99%